2016
DOI: 10.1007/s00417-016-3471-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for functional improvement following intravitreal bevacizumab injections after central retinal vein occlusion

Abstract: Intravitreal injections of bevacizumab in a routine clinical setting effectively improved and stabilized BCVA in CRVO. Our large multicenter study identified initial BCVA, baseline CRT, and pre-treatment as prognostic factors for visual improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The comparison between the two groups shows that the cured group is younger, has a shorter disease duration, has a greater proportion of BRVO, and has lower values of baseline CMT and baseline BCVA when compared with the uncured group. This is consistent with previous studies investigating the baseline indexes to predict the long-term efficacy in RVO-ME (26)(27)(28)(29)(30). Scott et al (31) have treated RVO-ME patients with anti-VEGF treatments for six consecutive (once a month) months, and the univariate regression analysis shows that the baseline BCVA and the baseline CMT are significantly correlated with 6-month BCVA.…”
Section: ) (E)supporting
confidence: 89%
See 2 more Smart Citations
“…The comparison between the two groups shows that the cured group is younger, has a shorter disease duration, has a greater proportion of BRVO, and has lower values of baseline CMT and baseline BCVA when compared with the uncured group. This is consistent with previous studies investigating the baseline indexes to predict the long-term efficacy in RVO-ME (26)(27)(28)(29)(30). Scott et al (31) have treated RVO-ME patients with anti-VEGF treatments for six consecutive (once a month) months, and the univariate regression analysis shows that the baseline BCVA and the baseline CMT are significantly correlated with 6-month BCVA.…”
Section: ) (E)supporting
confidence: 89%
“…The anti-VEGF drugs have been widely used in ocular diseases such as exudative age-related macular degeneration, diabetic macular edema, choroidal neovascularization, and RVO-ME, and have shown good safety and efficacy. Previous retrospective and prospective studies have shown that the anti-VEGF treatment for RVO-ME in real-word has achieved significant retinal structure improvement and visual function recovery ( 5 , 17 , 29 , 33 , 37 , 38 ). The patients included in this study are divided into the mAb group (ranibizumab injection) and the Fc group (injection of conbercept or aflibercept) according to their mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Januschowski et al treated patients with bevacizumab and looked at multiple baseline patient characteristics in a diagnosis of CRVO and found that a low BVA and high CRT were indicative of greater visual improvement at weeks 24 to 48. 14 These findings may be due to the increased capacity for recovery in patients with initially low BVA and high CRT.…”
Section: Discussionmentioning
confidence: 99%